Legal Protection For The Tapian Dolok Community Against The Negative Impact Of The Construction Of The Tebing Tinggi-Sinaksak Toll Road Se-tion - Azzahra, Destia; Khalid, Khalid (IHSA Institute, 2024)
In order to realize equitable national development, the government is aggressively building infrastructure in Indonesia. One of the infrastructure developments is the construction of toll roads. The purpose of this research is to provide legal protection for the Tapian Dolok community against the negative impact of the Tebing Tinggi-Sinaksak toll road construction. This research is a type of qualitative research that uses an empirical juridical legal approach. Data sources were obtained by interviewing several sources and analyzed with existing legal regulations. The results showed that there were many positive impacts that could be felt from the construction of this toll road. However, there were also people who experienced negative impacts from the construction of this toll road such as clogging of waterways resulting in flooding, some road structures were damaged due to large vehicles transporting toll road construction needs such as; building raw materials and building construction tools. Then, some MSME traders lost buyers